Disrupting Normative Femininity: Diagnoses of Eating Disorders as Tools of Control - de Welles, Madeleine (Canadian Woman Studies/les cahiers de la femme, 2023)
You don’t look like you have an eating disorder. Aren’t you supposed to be thin? This paper discusses representations of two eating dis-orders—binge eating disorder and anorexia—as they appear the Diagnostic and Statistical Manual of Mental Disorders—Fifth Edition (DSM-V). I discuss how such representations construct disorder, fatness, and cultural expectations of femininity. I suggest that feminist and fat studies, together with disability studies, complicate assumptions of eating disorders and fatness, while revealing how medicine, culture, and society enforce normative expectations of the body and its relationship with society.